Impact of a multi-criteria rating in e-commerce: the moderating effect of self-depletion on trust and purchase intention. (12th November 2019) - Schmit, Virgile; Baccino, Thierry
Self-depletion is known to have a wide range of effects on the decision-making process. Two experimental studies investigate whether a purchase decision-making on an e-commerce product webpage is affected by the state of self-depletion when using a multi-criteria rating scale. A questionnaire was built to measure trust, distrust and purchase intention and was submitted to one hundred and twenty-two participants (categorised in two groups according to their self-depletion test) who have to judge different mp3 (Mpeg Audio Layer 3) players presented on a webpage. In both studies, the variance of ratings were investigated with the presence of a global rating (1st exp.) and the valence of the global rating (2nd exp.) of the products. Main results show that self-depletion moderated the effect of variance of the ratings on the judgment and also lead to a polarisation effect. Trust and purchase intention are highly correlated, while distrust is only loosely correlated to purchase intention, supporting the view of a dual trust-distrust construct, instead of a continuum.